Iontophoresis-assisted corneal crosslinking using 0.1% riboflavin for progressive keratoconus - Jia, Hong-Zhen (Int J Ophthalmol, 2017)
AIM: To report the clinical results of iontophoresis-assisted epithelium-on corneal crosslinking (I-CXL) using 0.1% riboflavin in distilled water for progressive keratoconus. METHODS: In this prospective clinical study, we examined 94 eyes of 75 patients with progressive keratoconus who were treated with I-CXL using 0.1% riboflavin in distilled water. Best correct visual acuity (BCVA), Scheimpflug tomography, corneal topography, anterior segment optical coherence tomography, intraocular pressure, and endothelial cell density were evaluated at baseline and 1, 3, 6, 12, and 24mo after I-CXL. RESULTS: After 24mo I-CXL, compared to the level at baseline, BCVA significantly improved 0.14±0.07 (P=0.010); mean keratometry signifi-cantly decreased 0.72±1.97 (P=0.021); maximum keratometry significantly reduced 2.30±5.01 (P=0.014); central keratoconus index significantly reduced 0.04±0.08 (P=0.007). The demarcation line was visible in 83.1% of eyes at 1mo after treatment, with a depth of 298.95±51.97 µm, and gradually indistinguishable. One eye had repeat treatment. Intraocular pressure and endothelial cell density did not change significantly. CONCLUSION: I-CXL using 0.1% riboflavin halts keratoconus progression within 24mo, resulting in a significant improvement in visual and topographic parameters. Moreover, the depth of the demarcation line is similar to that previously reported in standard epithelium-off CXL procedures.